A review of the potential impacts of climate change on bulk power system planning and operations in the United States. (December 2018) - Craig, Michael T.; Cohen, Stuart; Macknick, Jordan; Draxl, Caroline; Guerra, Omar J.; Sengupta, Manajit; Haupt, Sue Ellen; Hodge, Bri-Mathias; Brancucci, Carlo
Abstract: Climate change might impact various components of the bulk electric power system, including electricity demand; transmission; and thermal, hydropower, wind, and solar generators. Most research in this area quantifies impacts on one or a few components and does not link these impacts to effects on power system planning and operations. Here, we advance the understanding of how climate change might impact the bulk U.S. power system in three ways. First, we synthesize recent research to capture likely component-level impacts of climate change in the United States. Second, given the interconnected nature of the electric power system, we assess how aggregated component-level impacts might affect power system planning and operations. Third, we outline an agenda for future research on climate change impacts on power system planning and operations. Although component-level impacts vary in their magnitude, collectively they might significantly affect planning and operations. Most notably, increased demand plus reduced firm capacity across generation types might require systems to procure significant additional capacity to maintain planning reserve margins, and regional declines in renewable resources might need to be offset by increasing zero-carbon investment to meet decarbonization targets. Aggregated impacts might also affect operations, e.g., through shifts in dispatching and increased operational reserve requirements. Future research should aggregate component-level impacts at operational timescales, quantify impacts on wind and solar variability, and contextualize climate change impacts within ongoing shifts in the electric power system. Highlights: Climate change might impact electricity demand, generation, and transmission. We discuss how these impacts might jointly impact planning and operations. Increased demand plus reduced firm capacity will require additional capacity. Regional declines in renewable resource will affect decarbonization efforts. Future research on aggregated component-level impacts is necessary.